Podophthalmus Vigil (Crustacea: Brachyura: Portunidae), a New Record of Marine Crab in Bangladesh - Chowdhury, Sayedur Rahman; Sadek, Md Abu; Mamun, Md Abdullah Al; Nazrul, KM Shahriar; Mamun, Al; Hossain, M Shahadat; Sharifuzzaman, SM (Bangladesh Journal of Zoology, 2020)
Abstract Not Available Bangladesh J. Zool. 48(1): 189-195, 2020